Responsive website for sentiment analysis - Li, Dan (2018)
Sentiment Analysis, also known as opinion mining, is to use Natural Language Processing methods to systematically identify, extract, quantify and study the subjective information. It has been used widely in analysing reviews in public media platforms, like Twitter, Sina Blog etc. In this project, it aims to implement Sentiment Analysis method into a survey platform. It is expected to analyse texture input and to provide an instant result about input’s subjective inform. The project contains two parts, where they are Sentiment Analysis Model building and Website development. Sentiment Analysis Model is built following ‘Opinion Word Expansion and Target Extraction through Double Propagation’ by Liu Bing. It is a lexicon-based approach which targets each individual texture input. Website development consists of website design and database management. This survey platform takes texture input formats, which its input should either be short sentence or paragraph. It is expected to be used in the areas like presentation marking, conference feedback or interview comments.